2022
DOI: 10.26748/ksoe.2022.028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydraulic Characteristics According to the Cross-Section Changes in Submerged Rigid Vegetation

Abstract: <i>Recently, not only Korea but also the world has been suffering from problems related to coastal erosion. The hard defense method has been primarily used as a countermeasure against erosion. However, this method is expensive and has environmental implications. Hence, interest in other alternative methods, such as the eco-friendly vegetation method, is increasing. In this study, we aim to analyze the hydraulic characteristic of submerged rigid vegetation according to the cross-sectional change through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In computational fluid dynamics (CFD) techniques, the porous structure effect has been considered in numerous ways. The modified Navier-Stokes equation including the resistance of the porous medium was defined as the governing equation, without directly modeling the porous structure [10,11]. Furthermore, the wave model and the seabedstructure dynamic model were combined; however, only a one-way coupling method has been used so far [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In computational fluid dynamics (CFD) techniques, the porous structure effect has been considered in numerous ways. The modified Navier-Stokes equation including the resistance of the porous medium was defined as the governing equation, without directly modeling the porous structure [10,11]. Furthermore, the wave model and the seabedstructure dynamic model were combined; however, only a one-way coupling method has been used so far [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of rigid vegetation has been represented in several previous studies describing the properties and configuration of the simulated vegetation (e.g., material used, thickness, and spacing). A summary review of rigid-weed simulations from the studies [29][30][31][32][33][34][35][36][37][38][39][40] was conducted, as shown in Table 2, to help select a suitable weed simulation for this research. Recently, Li et al [41] numerically studied the effect of one-sided bank vegetation on morphological change.…”
Section: Introductionmentioning
confidence: 99%